2013
DOI: 10.1002/da.22168
|View full text |Cite
|
Sign up to set email alerts
|

Is Dental Phobia a Blood-Injection-Injury Phobia?

Abstract: The present findings converge to the conclusion that dental phobia should be considered a specific phobia subtype independent of the B-I-I cluster within the DSM classification system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Dental anxiety was evaluated using the validated Hebrew version 45-48 of Corah's DAS 11,12 . In the DAS questionnaire, participants score their level of anxiety regarding four dental scenarios using a 5-point scale (total score range: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The DAS is a reliable and valid instrument, and the most extensively studied dental fear scale among adults 11,37,49 .…”
Section: Corah's Dasmentioning
confidence: 99%
“…Dental anxiety was evaluated using the validated Hebrew version 45-48 of Corah's DAS 11,12 . In the DAS questionnaire, participants score their level of anxiety regarding four dental scenarios using a 5-point scale (total score range: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The DAS is a reliable and valid instrument, and the most extensively studied dental fear scale among adults 11,37,49 .…”
Section: Corah's Dasmentioning
confidence: 99%
“…AS is associated with avoidance of preventive dental care, which can lead to poor oral health and increased risk of the development and maintenance of chronic medical conditions that are associated with oral disease, such as cardiovascular disease (Weiner, ). AS is associated with the presence of dental phobia (Kılıç, Ak, & Ak, ), and dental phobic individuals tend to visit the dentist less than once a year, which is below the clinical recommendation for adequate preventive dental care (van Houtem et al., ). Individuals with high AS may avoid dental care because they fear the possibility of experiencing anxiety‐related sensations or other types of unpleasant somatic sensations, such as pain, during dental procedures.…”
Section: Avoidance Of Healthy Activitiesmentioning
confidence: 99%
“…In support of this observation, Seligman (1971) found that human fears and phobias are not randomly distributed in the population, thus suggesting the presence of specific underlying mechanisms for fear development. Dental phobia is of particular interest in this regard as it is one of the most prevalent phobias and should be considered as a specific phobia (van Houtem et al, 2013). It is a remarkably severe condition with protracted duration and resistancy to treatment (Agras et al, 1969; Fiset et al, 1989; Ost, 1989, 1997; Oosterink et al, 2009).…”
Section: Introductionmentioning
confidence: 99%